A novel dendritic mesoporous silica based sustained hydrogen sulfide donor for the alleviation of adjuvant-induced inflammation in rats. (1st January 2021) - Yu, Yue; Wang, Zhou; Yang, Qinyan; Ding, Qian; Wang, Ran; Li, Zhaoyi; Fang, Yudong; Liao, Junyi; Qi, Wei; Chen, Keyuan; Li, Meng; Zhu, Yi Zhun
Abstract: Purpose: S-propargyl-cysteine (SPRC), an excellent endogenous hydrogen sulfide (H2 S) donor, could elevate H2 S levels via the cystathionine γ-lyase ( CSE)/H2 S pathway both in vitro and in vivo . However, the immediate release of H2 S in vivo and daily administration of SPRC potentially limited its clinical use. Methods: To solve the fore-mentioned problem, in this study, the dendritic mesoporous silica nanoparticles (DMSN) was firstly prepared, and a sustained H2 S delivery system consisted of SPRC and DMSN (SPRC@DMSN) was then constructed. Their release profiles, both in vitro and in vivo, were investigated, and their therapeutical effect toward adjuvant-induced arthritis (AIA) rats was also studied. Results: The spherical morphology of DMSN could be observed under scanning Electron Microscope (SEM), and the transmission electron microscope (TEM) images showed a central-radiational pore channel structure of DMSN. DMSN showed excellent SPRC loading capacity and attaining a sustained releasing ability than SPRC both in vitro and in vivo, and the prolonged SPRC releasing could further promote the release of H2 S in a sustained manner through CSE/H2 S pathway both in vitro and in vivo . Importantly, the SPRC@DMSN showed promising anti-inflammation effect against AIA in rats was also observed. Conclusions: A sustained H2 S releasing donor consisting of SPRC and DMSN was constructed in this study, and this sustained H2 S releasing donor might be of good use for the treatment of AIA.